Static and dynamic-wetting measurements on 3-aminopropyltriethoxysilane-functionalized float glass surfaces as a method for indicating adhesion forces - Patejdl, Sarah; Jung, Ulrich; Knoth, Christopher; Görrn, Patrick (Journal of Print and Media Technology Research, 2024)
Earlier research demonstrated the dependence of 3-aminopropyltriethoxysilane (APTES) wetting properties on cleaning, functionalization, and post-treatment processes on oxide surfaces, e.g., glass surfaces or Si wafer surfaces, but not on float glass surfaces. Also, oxide glass surfaces were functionalized by different silanes and were applied with ultraviolet (UV) radiation-curable inks or adhesives. The resulting adhesion forces differed depending on the silane and the UV-curable ink or adhesive used. The chemical diversity of silanes leads to different surface energy on glass surfaces and was used to gain further insights into a correlation between wetting properties and the resulting adhesion forces. This work investigates the suitability of dynamic contact angle measurement (DCA) for indicating adhesion forces via contact angle hysteresis and the resulting drop age. Two types of test fluids (diiodomethane and water) are applied on hydrophilic float glass surfaces (air side and tin side) and on a hydrophobic PE foil surface. The functionalization of glass substrates is realised by reproducible vapour and solution deposition of APTES, which results in different wetting properties of float glass surfaces. The investigations are complemented by static contact angle measurements of different test fluids, and the appropriate surface energies are evaluated via the Owens, Wendt, Rabel, and Kaelble method. The polar and non-polar surfaces are clearly differentiable by contact angle hysteresis and drop age. The DCA results of the hydrophilic float glass surfaces and the hydrophobic PE foil surface confirm the suitability of using the DCA parameters hysteresis and drop age for indicating adhesion forces on functionalized float glass surfaces. The hysteresis and drop age of assumed completely APTES-functionalized float glass surfaces confirm the suitability of the DCA measurement for indicating adhesion forces, too. The test fluid diiodomethane is suitable for indicating adhesion forces on the air side of the float glass, and the test fluid water is suitable for indicating adhesion forces on the tin side of the float glass. With the increased water contact angle, the hysteresis and drop age increased using the polar test fluid water. This does not support the polarity theory of de Bruyne. By using the non-polar test fluid diiodomethane, the hysteresis and drop age decrease with increasing contact angle and also do not support the adhesion theory of de Bryne. The research results show a way of indicating the adhesion forces of different functionalized float glass surfaces, by using only one silane, and serves as a pre-step for better understanding of e.g. UV-ink adhesion forces dependent on glass surface wetting properties.